2020
DOI: 10.1111/and.13841
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in reproductive parameters and gene expression in Balb/c mice testes after exposure to silver nanoparticles

Abstract: Mammalian spermatogenesis starts shortly after birth from spermatogonial stem cells, which have the ability to self-renew, followed by differentiation of spermatogonia and the ultimate production of spermatozoa. The complex process of spermatogenesis is highly sensitive to environmental insults, such as exposure to chemical and physical factors. Nanoparticles (NPs) are defined as substances with a diameter in the range of 1-100 nm (Beer, Foldbjerg, Hayashi, Sutherland, & Autrup, 2012). Silver nanoparticle (AgN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It has been shown that Ag NPs within the intracellular space has the potential to cause mitochondrial dysfunction by the depolarization of the mitochondrial membrane [ 97 , 99 ]. Wang et al reported damaged mitochondria in the testis upon Ag NP exposure to Balb/c mice [ 100 ]. These findings support the hypothesis in the biological plausibility perspective that Ag NPs interact with the thiol groups of the biomolecules, causing disruptions in the antioxidant system and thus triggering oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Ag NPs within the intracellular space has the potential to cause mitochondrial dysfunction by the depolarization of the mitochondrial membrane [ 97 , 99 ]. Wang et al reported damaged mitochondria in the testis upon Ag NP exposure to Balb/c mice [ 100 ]. These findings support the hypothesis in the biological plausibility perspective that Ag NPs interact with the thiol groups of the biomolecules, causing disruptions in the antioxidant system and thus triggering oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several in vivo studies demonstrate alterations in apoptosis-related gene expressions, increased ratio of Bax/Bcl-2 expressions ( 90 , 93 , 100 , 113 , 114 ) and mitochondria-dependent intrinsic apoptotic pathway in testes [ 93 , 113 ]. An extensive gene expression analysis conducted on 383 genes by microarray shows great changes in apoptosis-related genes and proteins (caspase3 and Myc).…”
Section: Resultsmentioning
confidence: 99%
“…Spermatogenesis is a long-term complex developmental process, 50 and any component changes may affect sperm development and maturation, resulting in abnormal sperm morphology and hypofunction. 51 Therefore, the normal histopathological structure of the testes is the basic requirement for long-term reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…Silver is used in water filtration, jewellery, solar panels, electrical contacts, conductors, coatings, chemical reactions and a colourant in glass. The studies about silver is mainly on nanoparticle exposure which reported a significant decrease in sperm motility and normal sperm morphology in rats (Baki et al, 2014) and decreased sperm production and changed testis morphology in mice (Wang et al, 2021) and induced oxidative stress in testis and epididymis; which adversely affect sperm parameters in rats and mice (Olugbodi et al, 2020). There is no previous study in the literature observing the correlation of Ag amount with sperm parameters.…”
Section: Discussionmentioning
confidence: 99%